Identifying health policy and systems research priorities for the sustainable development goals: social protection for health - Mary Qiu; Nasreen Jessani; Sara Bennett (BMC, 2018)
Abstract Background There is an established body of evidence linking systems of social protection to health systems and health outcomes. The Sustainable Development Goals (SDGs) provide further emphasis on this linkage as necessary to achieving health and non-health goals. Existing literature on social protection and health has focused primarily on cash transfers. We sought to identify potential research priorities concerning social protection and health in low and middle-income countries, from multiple perspectives. Methods Priority research questions were identified through two sources: 1) research reviews on social protection interventions and health, 2) interviews with 54 policy makers from Ministries of Health, multi-lateral or bilateral organizations, and NGOs. Data was collated and summarized using a framework analysis approach. The final refining and ranking of the questions was completed by researchers from around the globe through an online platform. Results The overview of reviews identified 5 main categories of social protection interventions: cash transfers; financial incentives and other demand side financing interventions; food aid and nutritional interventions; parental leave; and livelihood/social welfare interventions. Policy-makers focused on the implementation and practice of social protection and health, how social protection programs could be integrated with other sectors, and how they should be monitored/evaluated. A collated list resulted in 31 priority research questions. Scale and sustainability of social protection programs ranked highest. The top 10 research questions focused heavily on design, implementation, and context, with a range of interventions that included cash transfers, social insurance, and labor market interventions. Conclusions There is potentially a rich field of enquiry into the linkages between health systems and social protection programs, but research within this field has focused on a few relatively narrowly defined areas. The SDGs provide an impetus to the expansion of research of this nature, with priority setting exercises such as this helping to align funder investment with researcher effort and policy-maker evidence needs.